## Find y

Find y:

##
__
__**Hint**

**Hint**

Use basic algebra to solve to solve for unknowns.

##
__
__**Hint 2**

**Hint 2**

Use substitution to first solve for
$$x$$
.

Looking at the three equations, the variable
$$x$$
appears every time, meaning we should describe both the
$$y$$
and
$$z$$
variables in terms of
$$x$$
. Analyzing the second equation:

$$$x+z=0\rightarrow z=-x$$$

Analyzing the third equation:

$$$x-y=-5\rightarrow y=x+5$$$

Substituting the new equations into the original first equation:

$$$x+(x+5)+(-x)=2$$$

Solving for
$$x$$
:

$$$x=2-5=-3$$$

Since we now only have one unknown variable, we can solve for
$$y$$
using the third equation:

$$$y=-3+5=2$$$

2